Training and Socialization of Creative Gymnastics as a Medium for Strengthening Movement Literacy and Expression in Physical Education Learning for Teachers across Solo Raya - Aulia Maris; Baskoro Nugroho Putro; Putri Indah Nazareta; Agus Mukholid; Djoko Nugroho; Waluyo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Physical Education, Sports, and Health activities in the era of the Merdeka Curriculum require contextual, expressive, and movement literacy-based learning. However, Physical Education, Sports, and Health teachers' understanding of meaningful and creative learning approaches remains limited, particularly in implementing creative gymnastics. This program aimed to enhance Physical Education, Sports, and Health teachers’ knowledge, skills, and attitudes through hands-on, reflective training. The method employed a participatory-practice approach involving 70 teachers from various education levels across Solo Raya. Over two days, participants engaged in theoretical sessions, demonstrations, individual and group practice, as well as educational competition simulations. Evaluation results indicated a significant improvement in movement application aspects such as coordination, expression, and confidence in performing, with an average score increase of over 30%. Additionally, 91% of participants reported the activity as enjoyable and meaningful, while 90% expressed interest in further developing creative gymnastics. These findings suggest that the creative gymnastics-based approach is not only technically effective but also fosters value internalization and transforms teachers’ attitudes toward more reflective, participatory, and meaningful Physical Education, Sports, and Health learning. Therefore, creative gymnastics deserves to be positioned as a strategic pedagogical approach in contemporary Physical Education, Sports, and Health.